Induction of programmed cell death in Trypanosoma cruzi by Lippia alba essential oils and their major and synergistic terpenes (citral, limonene and caryophyllene oxide) - Érika Marcela Moreno; Sandra Milena Leal; Elena E. Stashenko; Liliana Torcoroma García (BMC, 2018)
Abstract Background Chagas Disease caused by Trypanosoma cruzi infection, is one of the most important neglected tropical diseases (NTD), without an effective therapy for the successful parasite eradication or for the blocking of the disease's progression, in its advanced stages. Due to their low toxicity, wide pharmacologic spectrum, and potential synergies, medicinal plants as Lippia alba, offer a promising reserve of bioactive molecules. The principal goal of this work is to characterize the inhibitory properties and cellular effects of the Citral and Carvone L. alba chemotype essential oils (EOs) and their main bioactive terpenes (and the synergies among them) on T. cruzi forms. Methods Twelve L. alba EOs, produced under diverse environmental conditions, were extracted by microwave assisted hydrodistillation, and chemically characterized using gas chromatography coupled mass spectrometry. Trypanocidal activity and cytotoxicity were determined for each oil, and their major compounds, on epimastigotes (Epi), trypomastigotes (Tryp), amastigotes (Amas), and Vero cells. Pharmacologic interactions were defined by a matrix of combinations among the most trypanocidal terpenes (limonene, carvone; citral and caryophyllene oxide). The treated cell phenotype was assessed by fluorescent and optic microscopy, flow cytometry, and DNA electrophoresis assays. Results The L. alba EOs displayed significant differences in their chemical composition and trypanocidal performance (p = 0.0001). Citral chemotype oils were more trypanocidal than Carvone EOs, with Inhibitory Concentration 50 (IC50) of 14 ± 1.5 μg/mL, 22 ± 1.4 μg/mL and 74 ± 4.4 μg/mL, on Epi, Tryp and Amas, respectively. Limonene exhibited synergistic interaction with citral, caryophyllene oxide and Benznidazole (decreasing by 17 times its IC50) and was the most effective and selective treatment. The cellular analysis suggested that these oils or their bioactive terpenes (citral, caryophyllene oxide and limonene) could be inducing T. cruzi cell death by an apoptotic-like mechanism. Conclusions EOs extracted from L. alba Citral chemotype demonstrated significant trypanocidal activity on the three forms of T. cruzi studied, and their composition and trypanocidal performance were influenced by production parameters. Citral, caryophyllene oxide, and limonene showed a possible induction of an apoptotic-like phenotype. The best selective anti-T. cruzi activity was achieved by limonene, the effects of which were also synergic with citral, caryophyllene oxide and benznidazole.